An interdisciplinary rehabilitation program for adults with dementia—A randomized controlled pilot trial evaluating social participation, loneliness and mental health - Josefine Lampinen; Håkan Littbrand; Ingeborg Nilsson; Annika Toots; Yngve Gustafson; Jerry Öhlin; Henrik Holmberg; Birgitta Olofsson; Anita Ericsson; Mia Conradsson (PLoS ONE, 2026)
Background To meet the complex needs of adults with dementia, a team-based, individualized rehabilitation approach may be required. This randomized controlled pilot trial evaluated the feasibility of a person-centred multidimensional interdisciplinary rehabilitation program for older adults with dementia, in terms of follow-up and response rates, and potential short- and long-term effects in adults with dementia on social participation, loneliness, and mental health. Methods Participants (mean age (SD) 78.7 (±6.6) years), were randomized to an intervention group (n = 31) or usual care (n = 30). The rehabilitation program consisted of a 20-week rehabilitation period and two follow-ups after 5 and 14 months. An interdisciplinary team performed assessments and interventions based on the individual’s goals. Assessors blinded to group allocation performed structured assessments at baseline and after 5, 12, 24, and 36 months. Results Initially, response rates in participants with dementia were high for all assessments in the areas of social participation, loneliness, and mental health. Response rates after 12 months decreased, particularly for cognitively demanding questions with multiple-choice options in the area of social participation. Overall, there were few statistically significant differences between the groups in the outcomes over 36 months, but some of the findings seemed potentially clinically meaningful in favor of the intervention group: increased frequency of active recreation and organized social activities outside the home, as reported by both participants with dementia and caregivers or staff; as well as experienced more frequent visits to family and friends; and short-term reduction in depressive symptoms. Conclusions Assessments made of loneliness and mental health in this study over three years seemed feasible. It seemed cognitively demanding for participants with dementia to answer questions regarding social participation over time; therefore it seemed worthwhile to also ask informal caregivers or staff to avoid data loss. The positive findings noted during assessments and potential effects indicate that it is relevant to proceed further to an adequately powered RCT and conducted in additional geographical regions. Trial registration ISRCTN – The UK’s Clinical Study Registry: http://www.isrctn.com/ISRCTN59155421